Management of patients with multiple myeloma and COVID-19 in the post pandemic era: a consensus paper from the European Myeloma Network (EMN) - Terpos, Evangelos; Musto, Pellegrino; Engelhardt, Monika; Delforge, Michel; Cook, Gordon; Gay, Francesca; van de Donk, Niels W C J; Ntanasis-Stathopoulos, Ioannis; Vangsted, Annette Juul; Driessen, Christoph; Schjesvold, Fredrik; Cerchione, Claudio; et al. (Leukemia, 2023)
In the post-pandemic COVID-19 period, human activities have returned to normal and COVID-19 cases are usually mild. However, patients with multiple myeloma (MM) present an increased risk for breakthrough infections and severe COVID-19 outcomes, including hospitalization and death. The European Myeloma Network has provided an expert consensus to guide patient management in this era. Vaccination with variant-specific booster vaccines, such as the bivalent vaccine for the ancestral Wuhan strain and the Omicron BA.4/5 strains, is essential as novel strains emerge and become dominant in the community. Boosters should be administered every 6-12 months after the last vaccine shot or documented COVID-19 infection (hybrid immunity). Booster shots seem to overcome the negative effect of anti-CD38 monoclonal antibodies on humoral responses; however, anti-BCMA treatment remains an adverse predictive factor for humoral immune response. Evaluation of the immune response after vaccination may identify a particularly vulnerable subset of patients who may need additional boosters, prophylactic therapies and prevention measures. Pre-exposure prophylaxis with tixagevimab/cilgavimab is not effective against the new dominant variants and thus is no longer recommended. Oral antivirals (nirmatrelvir/ritonavir and molnupiravir) and remdesivir are effective against Omicron subvariants BA.2.12.1, BA.4, BA.5, BQ.1.1 and/or XBB.1.5 and should be administered in MM patients at the time of a positive COVID-19 test or within 5 days post symptoms onset. Convalescent plasma seems to have low value in the post-pandemic era. Prevention measures during SARS-CoV-2 outbreaks, including mask wearing and avoiding crowded places, seem prudent to continue for MM patients.
Keywords: Consensus; neutralizující protilátky; Pandemics; lidé; mnohočetný myelom; Multiple Myeloma; COVID-19 Serotherapy; pandemie; Humans; Antibodies, Neutralizing; konsensus; sérologická léčba covidu-19; COVID-19; SARS-CoV-2